ANALISIS POTENSI PENINGKATAN PAD KOTA SEMARANG DARI PENYEWAAN ASET MILIK DAERAH KEPADA SWASTA - Hardiwinoto -; Akhmad Fathurohman; Ery Wibowo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The aim of this study is to investigate of the type of assets belonging to the government of Semarang City that can be leased to the private sector to increase investment passion. The research method is survey and data collection method of asset type owned by Government of Semarang City. The result of this research is finding all types of assets that can be leased to private parties, thus assisting the private sector in the development of investment and increasing of original revenue (Pendapatan Asli Daerah) of Semarang City. Keywords: assets, government, semarang